Postural Balance Ability and the Effect of Visual Restriction on Older Dancers and Non-Dancers - Nikolaidou, Maria-Elissavet; Karfis, Vasilios; Koutsouba, Maria; Schroll, Arno; Arampatzis, Adamantios (Frontiers in Sports and Active Living, 2021)
Dance is suggested as an advantageous exercise modality for improving postural balance performance and reducing risk of falls in the older population. Our main purpose was to investigate if visual restriction impacts older dancers and non-dancers differently during the quiet stance balance performance test. We hypothesized higher balance performance and greater balance deterioration due to visual restriction in dancers compared to non-dancers, indicating a superior contribution of the visual channel in the expected higher balance performance of dancers. Sixty-nine (38 males, 31 females, 74±6 years) healthy older adults participated and were grouped into a Greek traditional dance group (n=31, 2-3 times/week for 1.5 hours/session, minimum of 3 years) and a non-dancers control group (n=38, no systematic exercise history). Participants completed an assessment of one-legged quiet stance trials with both left and right leg with eyes open while standing barefoot on a force plate (Wii, Biovision, A/D converter, 1000 Hz), and two-legged trials with both eyes open or closed. Possible differences in anthropometric and one-legged balance parameters were examined with univariate ANOVA with group and sex as fixed factors. An ANOVA with the same fixed factors and vision as repeated measures factor were used for the two-legged balance parameters. In the one-legged task, the dance group showed significantly lower values in anteroposterior and mediolateral sway amplitudes (p=0.001 and p=0.035) and path length measured in both directions (p=0.001) compared to the non-dancers. In the two-legged stance we found a significant vision effect on path length (p<0.001) and anteroposterior amplitude (p<0.001) whereas the mediolateral amplitude did not differ significantly (p=0.439) between close and open eyes. The dance group had significantly lower CoP path length (p=0.006), anteroposterior (p=0.001) and mediolateral sway amplitude (p=0.003) both in eyes open and eyes closed trials compared to the control group. The superior balance performance in the two postural tasks found in dancers is possibly the result of dance’s coordinated, aesthetically-oriented intersegmental movements with alternation of one- and two-legged stance phases. Visual restriction resulted in similar deterioration of balance performance in both groups, thus suggesting that the visual channel’s contribution alone cannot explain the superior balance performance in dancers.